(3CQLhRI aj GdMce hGdCeKGds
(3ChdgG (B:s
(3CYhO HGddg ef GdTjWGf hGdMeO ddg Ydi GdEjeGf s
(3BNQgG (B:s
(3hUMHg GdCeGLO GdCHQGQ eG OQGJ GdCadGc aj GdCbWGQ s
(3GfXQgG eY eLehYI TYQjI ChdgG CQLhRI aj eYGfj eKdKGJ bWQH ef U` (B88 (3Edi U` (B93s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B20 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs